Circular Accounting and Regenerative Business Models: How Environmental Foresight Drives SME Competitive Advantage Through Dynamic Capabilities - Iman Supriadi; Rahma Ulfa Maghfiroh; Rukhul Abadi (Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, 2025)
This study aims to investigate the critical role of circular economy capabilities in enhancing SME competitiveness by developing an integrated theoretical framework that bridges dynamic capabilities theory with circular economy principles. Employing a rigorous quantitative research design, the study collected comprehensive data from SMEs operating across multiple industrial sectors in Indonesia. Advanced structural equation modeling techniques were applied to analyze the complex relationships between circular economy capabilities and competitive performance outcomes, while controlling for relevant contextual factors. This methodological approach ensures a robust examination of both direct effects and mediating mechanisms. The findings reveal that circular accounting literacy and regenerative business orientation enhance competitiveness through distinct pathways, with strategic environmental foresight playing a differential mediating role. Moreover, the study makes several novel contributions by developing an integrated capability framework for circular economy implementation, establishing circular accounting literacy as a fundamental SME competency, and demonstrating how specific capability configurations influence sustainable performance outcomes. These insights significantly advance both theoretical understanding and practical strategies for adopting circular business models within the SME sector.